Calcidiol serum levels and blood pressure responses in normotensive patients with dietary goat milk (Bangladesh Journal of Medical Science, 2018)
Background: Calcidiol (25-hydroxyvitamin D or 25(OH) D) is the active form of vitamin D that can be measured in the blood. Vitamin D functions as a regulator of blood pressure and a vitamin D deficiency is associated with an increased risk of hypertension. Goat’s milk is thought to have anti hypertensive effect. That is likely due to the amount of vitamin D found in goat’s milk, but requires further investigation. This research was conducted to analyze the effect of consuming goat’s milk on blood pressure and its relationship with calcidiol serum in normotensive patients.Materials and Methods: The design of this research was experimental laboratory with randomized pretest-posttest with a control group using 18 sedentary women aged 18-19 years. The treatment was 250 ml/day of goat’s milk given in the morning after breakfast for 110 days. The data were analyzed by the statistical t-test (p